Probiotic Antibacterial Activity Test Of Bali Salak Fruit (Salacca zalacca var Amboinensis) Against Staphylococcus aureus - Istri Mas Padmiswari Anak Agung; Nadya Treesna Wulansari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
One of the sources of natural antioxidants comes from salak fruit (Salacca zalacca). Indonesia has various varieties of salak fruit such as pondoh salak, manggala salak, granulated sugar and balinese salak. Bali salak is one of the local Balinese salak varieties. This study aims to determine the probiotic antibacterial activity test of Balinese salak fruit juice against Staphylococcus aureus. The method used in this study was Completely Randomized (CRD) in laboratory scale experiments (in vitro). Laboratory-scale in vitro research was carried out at the ITEKES Bali Food Engineering and Processing Laboratory and the Agricultural Technology Laboratory at Udayana University which will be carried out between August 2021 and October 2021. Testing for antibacterial activity uses the well diffusion method. NA media containing Staphylococcus aureus isolates. Data analysis used analysis of variance (ANOVA). The results of the study found that Staphylococcus aureus bacteria could be prevented by using a probiotic drink, zalacca juice.